Exploring Mediating Motivations for Muslims’ Electoral Preferences: Issue Voters Rather Than Ideologues - Azabar, Samira; Thijssen, Peter (Politics of the Low Countries, 2025)
Research has revealed that a significant part of Muslims cast a vote for a left party, on the one hand, and/or a preferential vote(s), on the other, but the underlying explanatory factors remain unclear. Based on mediation analyses, we test whether the ‘left-wing tendency and personalization of the Muslim vote’ are motivated by specific considerations related to the Michigan model (issues, candidates, party evaluation) and/or minorities-specific factors (religion and political alienation) vis-à-vis non-Muslims. For this purpose, we focus on the electoral preferences of Muslims in Belgium based on mock ballot data connected to an exit poll for the Belgian local elections in 2018. Our structural equation analyses reveal that issues are particularly relevant for Muslims compared with non-Muslims when explaining the leftist vote. Furthermore, neither the Michigan model nor the minorities-specific variables seem to explain Muslims’ preferential voting vis-à-vis non-Muslims. Consequently, using in-depth interviews with Muslims, we further unravel these motivations and the decision-making process leading to their vote choices.